Whole exome sequencing identifies clinically relevant mutational signatures in resected hepatocellular carcinoma. Issue 1 (27th May 2020) - Chan, Jason Y.; Lim, Abner H.; Boot, Arnoud; Lee, Elizabeth; Ng, Cedric C.‐Y.; Lee, Jing Y.; Rajasegaran, Vikneswari; Liu, Wei; Goh, Shane; Hong, Jing H.; Xu, Xiaoying; Bharwani, Lavina D.; et al.
Abstract: Background & Aims: Most patients develop recurrent disease despite curative surgery for hepatocellular carcinoma (HCC). No standard adjuvant therapy is available and molecular predictors of outcome are poorly understood. Methods: We conducted a multicentre pilot study on patients with localized HCC following surgical resection. Patients received up to 6 months of oral gefitinib as adjuvant therapy. Clinical end points included recurrence‐free survival (RFS) and overall survival (OS), and exploratory analyses were conducted from whole exome sequencing data. Results: A total of 65 patients were screened for the study, of which 40 were eligible. The median age was 63 years (range, 44‐80). Most patients (80%) were positive for hepatitis B or C. With a median follow‐up of 4.5 years, the median RFS was 24 months. Median OS was not reached. High Child‐Pugh score and advanced T‐stage (3‐4) were independent predictors for both OS and RFS. Mutational signatures for exposure to aristolochic acid (AA), as characterized by a majority of T:A > A:T mutations, were observed in 18 cases (55%). HCC without AA mutagenesis was associated with early recurrences or death within 2 years of surgery ( P  = .037). HCC with high T > A mutations was associated with better OS (HR 0.29, 95% CI 0.09‐0.90, P  = .033). Conversely, HCC with high C > T mutations was associated with worse OS (HR 4.55, 95% CI 1.20‐17.31, P  = .026). Conclusions: Mutational signatures may carry prognostic significance in HCC following curative resection. Patient outcomes with gefitinib as adjuvant therapy after resection for HCC were modest, highlighting the need for urgent research in this area of unmet clinical need. ClinicalTrials.gov number, NCT00282100.